Aqueous Oxidative Heck Reaction as a Protein‐Labeling Strategy. Issue 2 (20th December 2013) - Ourailidou, Maria Eleni; van der Meer, Jan‐Ytzen; Baas, Bert‐Jan; Jeronimus‐Stratingh, Margot; Gottumukkala, Aditya L.; Poelarends, Gerrit J.; Minnaard, Adriaan J.; Dekker, Frank J.
Abstract An increasing number of chemical reactions are being employed for bio‐orthogonal ligation of detection labels to protein‐bound functional groups. Several of these strategies, however, are limited in their application to pure proteins and are ineffective in complex biological samples such as cell lysates. Here we present the palladium‐catalyzed oxidative Heck reaction as a new and robust bio‐orthogonal strategy for linking functionalized arylboronic acids to protein‐bound alkenes in high yields and with excellent chemoselectivity even in the presence of complex protein mixtures from living cells. Advantageously, this reaction proceeds under aerobic conditions, whereas most other metal‐catalyzed reactions require inert atmosphere.